The possibilities of immunohistochemistry for assessing the pathogenetic mechanisms of action of compounds with a suspected antitumor effect. Part I. General indicators of the process activity - M. A. Akimenko; O. A. Voronova; M. S. Alkhuseyn-Kuliaginova; A. B. Alnikin; N. A. Kornienko; M. A. Dodokhova; M. V. Gulyan; I. M. Kotieva (Фундаментальная и клиническая медицина)
Despite the wide arsenal of chemotherapeutic agents, the search and study of new compounds with an alleged antitumor effect is relevant. Morphological diagnostics of pathological processes occurring under the action of pharmacologically active substances is the most important component of preclinical research of compounds with an alleged antitumor effect. It is advisable to use information about the possible cytotoxic effect of candidates for antitumor drugs using an immunohistochemical method for studying organs and systems of experimental animals at different stages of the development of the tumor process by indirect markers of tumor progression activity. Morphological examination of parenchymal organs and tumor tissue in the dynamics of the development of malignant neoplasm is more informative and evidence-based than biochemical research. The aim of the study is to conduct a comparative analysis of markers of tumor process activity for more effective use of morphological and immunohistochemical research methods in the preclinical study of compounds with suspected antitumor activity to assess the prospects for their use with the detection of tumor process activity. The literature search was carried out using the Scopus, Web of Science, PubMed and eLIBRARY databases. The paper presents an overview of current molecular biological markers for assessing the activity of the malignant process in the experiment: Transforming Growth Factor beta 1 (TGF-β1), Ki-67, Tumor necrosis factor alpha (TNF-α), p53, Poly-ADP-ribose polymerase 1 (PARP-1) and Anti-8-Hydroxy-2'-deoxyguanosine (8-OHdG), beta III Tubulin, p120 Catenin, Beta Actin. The listed markers are indirect and can be used in a single mode only for screening studies of antitumor and antimetastatic activity in which a large number of compounds are sorted according to the principle of effectiveness. When conducting an in-depth study of the pharmacological activity of the leader compounds it is necessary to perform a comprehensive immunohistochemical study. Our analysis of the literature data confirms the importance of selecting optimal, sensitive, economically feasible and affordable markers, which in turn leads to the improvement of diagnostic panels and their standardization to simplify their transition into clinical practice.